Formative assessment from the perspective of complexity in Design and Architecture project teaching - Manolio, Patrícia Adriana Marques de Andrade; Ferreira, Claudio Lima (DAT Journal, 2026)
The use of formative assessment promotes the development of important student skills, such as autonomy and critical and continuous reflection on knowledge, thereby fostering better interaction between teaching, learning, and assessment. This study seeks to analyze the use of formative assessment in design and architecture project teaching from the perspective of complexity, with an emphasis on the epistemological operators proposed by Edgar Morin. It is assumed that assessment should be understood as an integral part of the teaching-learning process, and not just from a simplistic, merely numerical, and classificatory perspective. This is a theoretical, qualitative study based on a literature review and conceptual analysis. The study seeks to conduct a comparative analysis between the two theoretical frameworks, aiming to identify convergences, complementarities, and tensions. The results obtained suggest that a formative assessment based on complexity operators contributes to teaching and learning design.